2020
DOI: 10.1002/hpm.2981
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the proportionate mortalities attributed to noncommunicable diseases in sub‐Saharan Africa for the period 2000 to 2016

Abstract: Summary Noncommunicable diseases (NCDs) remain a growing global health issue and sub‐Saharan Africa (SSA) is no exception. Using secondary data obtained from the World Bank on 48 SSA countries, we describe the trends in the proportionate mortalities attributed to NCDs in SSA between 2000 and 2016. The baseline proportionate mortalities attributed to NCDs in SSA increased from 22.49% in 2000 to 33.69% in 2016, representing about 11% increase. The trend was replicated across the low‐, middle‐, and high‐income co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The novelty of this study is that it is the only analysis conducted in SSA of the association of commonly-used lipid metrics with CVD endpoints. This is important because it is known that CVD prevalence is increasing in this region [ 56 , 57 ] and globally, 80% of deaths related to CVD occur in low- and middle-income countries [ 2 ]. In addition, the INTERHEART study demonstrated that premature acute myocardial infarction occurred more often in countries within SSA than in any of the other 52 countries included in that study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of this study is that it is the only analysis conducted in SSA of the association of commonly-used lipid metrics with CVD endpoints. This is important because it is known that CVD prevalence is increasing in this region [ 56 , 57 ] and globally, 80% of deaths related to CVD occur in low- and middle-income countries [ 2 ]. In addition, the INTERHEART study demonstrated that premature acute myocardial infarction occurred more often in countries within SSA than in any of the other 52 countries included in that study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%